2022
DOI: 10.1002/art.42282
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Bimekizumab in Patients With Active Ankylosing Spondylitis: Three‐Year Results From a Phase IIb Randomized Controlled Trial and Its Open‐Label Extension Study

Abstract: and Désirée van der Heijde 11Objective. To assess the long-term safety, tolerability, and efficacy of bimekizumab in patients with active ankylosing spondylitis (AS).Methods. Patients with active AS who completed the dose-ranging, 48-week BE AGILE randomized controlled trial were eligible to participate in an open-label extension (OLE) study, in which patients received 160 mg of bimekizumab every 4 weeks. We present the safety and efficacy results through 156 weeks. Missing efficacy data were imputed using non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Our analysis showed that, at a group level, disease activity and HRQoL remained stable through the COVID-19 pandemic. This was consistent with the sustained and stable efficacy of bimekizumab reported for up to 3 years of treatment (12,15), which followed the improvements in efficacy outcomes achieved in the first 12 and 48 weeks (11). We also found that there were no notable increases in missed study assessments during the pandemic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis showed that, at a group level, disease activity and HRQoL remained stable through the COVID-19 pandemic. This was consistent with the sustained and stable efficacy of bimekizumab reported for up to 3 years of treatment (12,15), which followed the improvements in efficacy outcomes achieved in the first 12 and 48 weeks (11). We also found that there were no notable increases in missed study assessments during the pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Bimekizumab, a monoclonal immunoglobulin G1 antibody that selectively inhibits interleukin-17F, in addition to interleukin-17A, to date has demonstrated clinically meaningful and sustained efficacy and was well tolerated in patients with active AS treated for up to 3 years in the phase 2b BE AGILE study and its ongoing open-label extension (OLE) (11)(12)(13). At the start of the pandemic in March 2020, patients were in the OLE receiving 160 mg of subcutaneous bimekizumab every 4 weeks (Q4W); most had received more than 3 years of bimekizumab treatment and outcomes were stable.…”
Section: Introductionmentioning
confidence: 99%
“…13 15-17 In the phase 2b BE AGILE trial in patients with active ankylosing spondylitis and its open-label extension, bimekizumab 160 mg every 4 weeks led to rapid disease control compared with placebo, with efficacy sustained for up to 3 years of treatment. 18 19 Here, we present the first phase 3 efficacy and safety data for bimekizumab across the full axSpA spectrum from two parallel trials in patients with nr-axSpA (BE MOBILE 1) and r-axSpA (BE MOBILE 2).…”
Section: Spondyloarthritismentioning
confidence: 99%
“…TEAEs, SAEs and prespecified safety topics of interest are defined in the online supplemental appendix. Adverse events were coded according to the Medical Dictionary for Regulatory Activities (MedDRA V. 19…”
Section: Endpointsmentioning
confidence: 99%
“…In the parallel phase 3 studies BE MOBILE 1 (nr-axSpA) and BE MOBILE 2 (r-axSpA), patients receiving subcutaneous 160 mg BKZ Q4W achieved the primary and all ranked secondary endpoints at Week 16 22. At Week 24, no new safety signals were observed with BKZ treatment, compared with the 3-year phase 2b BE AGILE study of BKZ in r-axSpA 23. Here, we present the clinical efficacy and safety of BKZ in patients with active axSpA up to Week 52 of BE MOBILE 1 and BE MOBILE 2.…”
Section: Introductionmentioning
confidence: 99%